Photosynthesis and photoprotective strategies in Laurus nobilis L. and Quercus ilex L. under summer drought and winter cold - Arena, C.; Vitale, L.; Virzo De Santo, A. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2008)
Abstract Photosynthesis and photoprotective mechanisms were investigated in the field on Laurus nobilis L. and Quercus ilex L. leaves exposed to summer drought (July) and winter cold (February) conditions compared with no-stress conditions (May). In July, net photosynthetic rate (A) and stomatal conductance (g s) decreased significantly compared with May in both species; conversely the highest ETR/A ratio and no difference in non-photochemical quenching (NPQ) was observed. In February A, g s and ETR/A declined compared with May but the highest NPQ were found in both species. Our data suggest that during summer, an increase of photochemical alternative pathways to carbon reduction, were able to effectively protect the photosynthetic apparatus under drought. In winter, the thermal dissipation of excess absorbed light constitutes the main safety valve for the photosynthetic apparatus.
doi: 10.1080/11263500802410819doi: 10.1080/11263500802410819The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Dissipative processes; L. nobilis; leaf gas-exchange; Q. ilex; summer drought; winter cold

Photosynthesis and photoprotective strategies in Laurus nobilis L. and Quercus ilex L. under summer drought and winter cold - Arena, C; Vitale, L; Virzo de Santo, A (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2008)
Abstract Photosynthesis and photoprotective mechanisms were investigated in the field on Laurus nobilis L. and Quercus ilex L. leaves exposed to summer drought (July) and winter cold (February) conditions compared with no-stress conditions (May). In July, net photosynthetic rate (A) and stomatal conductance (g s) decreased significantly compared with May in both species; conversely the highest ETR/A ratio and no difference in non-photochemical quenching (NPQ) was observed. In February A, g s and ETR/A declined compared with May but the highest NPQ were found in both species. Our data suggest that during summer, an increase of photochemical alternative pathways to carbon reduction, were able to effectively protect the photosynthetic apparatus under drought. In winter, the thermal dissipation of excess absorbed light constitutes the main safety valve for the photosynthetic apparatus.
doi: 10.1080/11263500802410819
Keywords: Dissipative processes; L. nobilis; leaf gas-exchange; Q. ilex; summer drought; winter cold